Selected readings in educational leadership: the challenges and issues in Muslim educational institutions - Othman, Azam (Institut Terjemahan & Buku Malaysia Berhad, 2016)
This book offers students of educational management and leadership the most current thinking and the exploration of educational leadership; as it relates to educational changes, leadership, performance appraisal, learning culture and parental involvement in schools. The most interesting plus-point is that the concept of leadership shared here is about the Islamic perspective of educational leadership. The contents of this book are generated from the collections of studies by the researchers form every corners of the Muslim World such as South East Asia, South Asia and West Africa. Containing chapters contributed by professors, associate professors, senior lecturers and postgraduate students. This comprehensive volume is an invaluable resource for young researchers, postgraduate students and educational leaders wanting to understand current issues and challenges faced by educational leaders in Muslim educational institutions.